Epstein-Barr virus (EBV) subtype in EBV related oral squamous cell carcinoma in Okinawa, a subtropical island in southern Japan, compared with Kitakyushu and Kumamoto in mainland Japan. Issue 6 (1st June 2002) - Higa, M; Kinjo, T; Kamiyama, K; Iwamasa, T; Hamada, T; Iyama, K
Abstract : Aim: In Okinawa, a subtropical island located between the East China Sea and Pacific Ocean, 2000 km south of mainland Japan, the incidence of oral squamous cell carcinoma is 1.5 times higher than that seen in mainland Japan, and a large number of these patients have been reported to be infected with the Epstein-Barr virus (EBV). This study aimed to gain a better understanding of the pathogenesis of this malignancy in this area by carrying out genomic analysis of EBV. Methods: Fifty four patients with oral squamous cell carcinoma reported from 1997 to 1999 in Okinawa were compared with 21 and 20 patients from Kitakyushu and Kumamoto in Kyushu, mainland Japan, respectively. Diagnosis was confirmed by conventional histological examination of paraffin wax sections. EBV was detected by non-isotopic in situ hybridisation (NISH) and the polymerase chain reaction (PCR) (Bam HI-F, EBV nuclear antigen 2 (EBNA2), and latent membrane protein 1 (LMP-1) regions). Sequence analysis of the PCR products was also carried out. Results: In Okinawa, 25 patients were found to be infected with EBV type A by analysing the 3′ sequence divergence of the EBNA2 genes. Six patients were positive for EBV type B, and eight for both type A and B. Therefore, type A virus infection was demonstrated in 33 of 54 patients, and type B in 14 of 54. In total, 39 of 54 patients were infected with EBV. However, the "f" variant was shown in only one patient, who was also infected with type A virus. In contrast, 97.0% of EBV type A infected patients showed a 30 bp deletion of the LMP-1 gene, but those infected with EBV type B did not. Sequence analysis of the type A virus EBNA2 gene revealed slight variations of the sequence (mutations)— 48991 G→T and 48998 C→A—in 18 of 33 cases compared with the B95-8 strain, and in 14 cases, in addition to these, a further mutation of 48917 T→C was demonstrated; in the single remaining case, only one mutation at 49137 A→G was detected. The mutations at 48991 (G→T), and 49137 (A→G) are associated with amino acid changes Arg→Met and Thr→Ala, respectively. In contrast, no mutation was seen in the EBNA2 DNA from the 14 cases of type B virus when compared with that of the Jijoye strain. In Kitakyushu and Kumamoto, only 10 of 41 patients (six in Kitakyushu and four in Kumamoto) were infected with EBV. Among them, nine patients were infected with type A virus, and only one patient from Kitakyushu was infected with type B virus. The 48991 G→T and 48998 C→A mutations of the EBNA2 region were demonstrated in type A virus, but the 48917 T→C and 49137 A→G mutations were not when compared with the B95-8 strain. In the case of type B virus no mutation was noted. A 30 bp deletion was found in these nine cases of type A, but not in type B. The sequence analysis of EBV type A in Okinawa, Kitakyushu, and Kumamoto showed slight variations when compared with B95–8, but EBV type B LMP-1 did not when compared with the Jijoye strains. Conclusion: In Okinawa, EBV infection was frequently demonstrated in oral squamous cell carcinoma (p < 0.001). However, in mainland Japan there was no significant correlation between EBV and oral squamous cell carcinoma. In Okinawa, EBV type B infection is approximately 10 times more common than in the mainland. However, in these areas—Okinawa, Kitakyushu, and Kumamoto—the frequency of the "f " variant was very low, whereas a high incidence of a 30 bp deletion of LMP-1 was noted. The number of EBV (including type A and/or B) infected oral squamous cell carcinomas in Okinawa was about three times higher than that seen in the mainland, although the frequency of oral squamous carcinoma was only 1.5 times higher than that seen in the mainland. A high prevalence of type B virus infection and slight differences in the EBNA2 gene sequence in the type A virus might influence the frequency of this carcinoma in Okinawa.